Randomized Controlled Trial of Adalimumab in Patients With Nonpsoriatic Peripheral Spondyloarthritis - Mease, Philip (Arthritis Rheumatol, 2015)
OBJECTIVE: To evaluate the efficacy and safety of adalimumab in patients with active nonpsoriatic peripheral spondyloarthritis (SpA). METHODS: ABILITY-2 is an ongoing phase III, multicenter study of adalimumab treatment. Eligible patients age ≥18 years fulfilled the Assessment of SpondyloArthritis international Society (ASAS) classification criteria for peripheral SpA, did not have a prior diagnosis of psoriasis, psoriatic arthritis (PsA), or ankylosing spondylitis (AS), and had an inadequate response or intolerance to nonsteroidal antiinflammatory drugs (NSAIDs). Patients were randomized 1:1 to receive adalimumab 40 mg every other week or matching placebo for 12 weeks, followed by a 144-week open-label period. The primary end point was the proportion of patients achieving 40% improvement in disease activity according to the Peripheral SpA Response Criteria (PSpARC40) at week 12. This was defined as ≥40% improvement from baseline (≥20-mm absolute improvement on a visual analog scale) in patient's global assessments of disease activity and pain, and ≥40% improvement in at least one of the following features: swollen joint and tender joint counts, total enthesitis count, or dactylitis count. Adverse events were recorded throughout the study. RESULTS: In total, 165 patients were randomized to a treatment group, of whom 81 were randomized to receive placebo and 84 to receive adalimumab. Baseline demographics and disease characteristics were generally similar between the 2 groups. At week 12, a greater proportion of patients receiving adalimumab achieved a PSpARC40 response compared to patients receiving placebo (39% versus 20%; P = 0.006). Overall, improvement in other outcomes was greater in the adalimumab group compared to the placebo group. The rates of adverse events were similar in both treatment groups. CONCLUSION: Treatment with adalimumab ameliorated the signs and symptoms of disease and improved physical function in patients with active nonpsoriatic peripheral SpA who exhibited an inadequate response or intolerance to NSAIDs, with a safety profile consistent with that observed in patients with AS, PsA, or other immune-mediated diseases.